2003
DOI: 10.1002/app.11931
|View full text |Cite
|
Sign up to set email alerts
|

Elongational rheology of LLDPE / LDPE blends

Abstract: ABSTRACT:The objective of this study is to investigate the effect of low density polyethylene (LDPE) content in linear low density polyethylene (LLDPE) on the crystallinity and strain hardening of LDPE / LLDPE blends. Three different linear low density polyethylenes (LL-1, LL-2 and LL-3) and low density polyethylenes (LD-1, LD-2 and LD-3) were investigated. Eight blends of LL-1 with 10, 20, 30 and 70 wt % of LD-1 and LD-3, respectively, were prepared using a single screw extruder. The elongational behavior of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 13 publications
0
37
0
1
Order By: Relevance
“…= 178.5(0.9644) Pe/ w (7) Although this empirical relation has no theoretical background, it has been proved that numerous data follow Eq. (7) [57].…”
Section: Capillary Extrusionmentioning
confidence: 91%
See 1 more Smart Citation
“…= 178.5(0.9644) Pe/ w (7) Although this empirical relation has no theoretical background, it has been proved that numerous data follow Eq. (7) [57].…”
Section: Capillary Extrusionmentioning
confidence: 91%
“…They found that zero-shear viscosity of the blends exhibits positive deviation from the logadditive rule. Later, Ajji et al [7] found that LDPE/LLDPE blends containing 10-20 wt% of LDPE show marked strain-hardening behavior in elongational viscosity. Wagner et al [8] also demonstrated that the strain-hardening behavior for LDPE/LLDPE is more pronounced than that for pure LDPE.…”
Section: Introductionmentioning
confidence: 97%
“…Compared to PP, HDPE shows greater deformity and the strain hardening at the lower slope. In the elastic region, deformation force is not sufficient to generate pores while as in plastic zone, lamellae, an increased elongation broadens pore size . Zuo et al .…”
Section: Membrane Preparation Techniquesmentioning
confidence: 99%
“…They are also widely being used in the film industry to enhance bubble stability during tubular film extrusion taking advantage of the superior physical properties of LLDPE. However, in spite of these efforts, a review of previous investigations to understand various aspects of polyolefin blends, such as miscibility and phase separation, processability and strain hardening, crystallization, and mechanical behavior reveals the complexity of the problem and highlights the need for further research …”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of these efforts, a review of previous investigations to understand various aspects of polyolefin blends, such as miscibility and phase separation, processability and strain hardening, crystallization, and mechanical behavior reveals the complexity of the problem and highlights the need for further research. [3][4][5][6][7][8][9][10] The modification of polyolefins has been intensely developed in the last decade because it is a relatively easy and economical method of increasing the range of application of mass-produced materials such as polyethylene (PE) and polypropylene. Moreover, for improving the processability of LLDPE, several new technologies have been developed in film-blowing process, such as spiral dies, dual lip air ring technology, lower pressure, grooved barrel feed sections, and high efficiency barrier screws.…”
Section: Introductionmentioning
confidence: 99%